Distribution and Habitat Preference of Hispid Hare (Caprolagus Hispidus) In Shuklaphanta National Park, Nepal - Chand, Dhirendra Bahadur; Khanal, Laxman; Chalise, Mukesh Kumar (Tribhuvan University Journal, 2017)
Hispid hare (Caprolagu shispidus) is an endangered lagomorph which had a wide range of distribution in the past, but currently it is known to occur only from few isolated tall grass pockets of India and Nepal. We explored the population status, habitat utilization and existing threats of the Hispid hare at Shuklaphanta National Park (SNP) by the strip transect and quadrate sampling methods from November 2015 to May 2016 covering both winter and summer seasons. Four study sites of total 1.58ha were selected within SNPand strip transects were randomly laid to determine presence and absence of pellets of Hispid hare and their counts were used to estimate the population density. The Population density of Hispid hare was found to be 0.1820/ha in winter and 0.2268/ha in summer with the statistically significant preference to the tall grassland habitat. Twelve grass species were identified in the habitat of Hispid hare with dominancy of Saccharum spontaneum, Imperata cylindrica, Narenga porphyrocoma, and Saccharum munj. Among the grasses, Imperata cylindrica and Narenga porphyrocoma were the food species of higher preference for Hispid hare.